2004
DOI: 10.1007/s10152-004-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Associational resistance of fouled blue mussels (Mytilus edulis) against starfish (Asterias rubens) predation: relative importance of structural and chemical properties of the epibionts

Abstract: Several epibiotic species reduce starfish (Asterias rubens) preference for the blue mussel Mytilus edulis in the Baltic. The aim of this study was to reveal whether this associational resistance was caused by structural or chemical aspects of the different epibionts. To assess structural epibiont effects, an in situ experiment was conducted with unfouled mussels and mussels equipped with artificial epibionts ('dummies') exposed to natural predation by A. rubens. The chemically inert dummies closely matched the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Kautsky & van der Maarel 1990, Reusch & Chapman 1997. Adult crabs and sea stars, however, consume mussels only to the threshold size of 48 mm shell length, beyond which size refuge is obtained (Sommer et al 1999, Enderlein et al 2003, Laudien & Wahl 2004. The protective effect could be due to large size, strong adductor muscles and/or more robust shells.…”
Section: Introductionmentioning
confidence: 99%
“…Kautsky & van der Maarel 1990, Reusch & Chapman 1997. Adult crabs and sea stars, however, consume mussels only to the threshold size of 48 mm shell length, beyond which size refuge is obtained (Sommer et al 1999, Enderlein et al 2003, Laudien & Wahl 2004. The protective effect could be due to large size, strong adductor muscles and/or more robust shells.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to sponge encrustation, barnacle encrustation can be seen as a case of ''shared doom'' since predation risk increased for scallops with one or more large barnacles. The mechanism by which this occurs is different than those previously described in the literature however (see Laudien & Wahl, 2004). Shared doom often occurs when an epibiont attracts predators either optically or chemically, making predation on its host more likely.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, Laudien & Wahl (2004) found that epibiont chemical deterrence, rather than structural/mechanical properties, was the primary mechanism protecting blue mussels from predation by Asterias rubens. This could reflect a difference in the motile vs. sessile lifestyles of scallops compared to mussels.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Indirect interactions occur via two basic ways (Wootton 1993): (1) due to linked direct interactions between species pairs (i.e., interaction chain) and (2) when a third species change how a pair of other species interact (i.e., interaction modification). By modifying the body surface properties of an organisms through tactile, visual, or chemical cues, epibionts can attract or repel predators, modulating in this way consumer-prey interactions (e.g., Wahl and Hay 1995;Wahl et al 1997;Laudien and Wahl 2004).…”
Section: Introductionmentioning
confidence: 99%